(untitled) (Journal of Pharma Insights and Research, 2024)
Analytical method development and validation are continuous and interdependent tasks associated with research & development, quality control, and quality assurance departments. Analytical procedures play a critical role in equivalence risk assessment and management, helping establish product-specific acceptance criteria and stability of results. Validation determines the suitability of an analytical procedure for its intended purpose. Literature surveys reveal various analytical methods based on UV spectrophotometry for determining Levetiracetam in bulk and in combination with different drugs. The parameters were validated according to ICH guidelines in terms of accuracy, precision, robustness, ruggedness, and other components of analytical validation. The developed methods are simple, sensitive, and reproducible, suitable for the analysis of Levetiracetam in bulk and tablet dosage forms